Analysis of In–P based 1.55 µm electrically pumped vertical-external-cavity surface-emitting lasers - Yap, David F W; Low, Andy L Y; Koh, S P; Tiong, S K (IOP PUBLISHING LTD, 2007)
In this paper, theoretical analysis of the In - P based 1.55 mu m electrically pumped vertical- external- cavity surface- emitting lasers is presented. Computational experimental results show that short- cavity VCSELs ( vertical- cavity surface- emitting lasers) with weak external feedback exhibit an increase of 37% output power compared with the conventional VCSELs. In addition, with an optimized external feedback, the - 3 dB modulation bandwidth can be increased by approximately 5% and having a wider eye opening in a 40 Gbit s(-1) transmission system.